Study of Family Functioning as a Predictor of Quality of Life in Caregivers of Individuals with Alcohol Dependence Syndrome - Hunny Kalra; Suninder Tung (Indian Journal of Social Psychiatry, 2025)
Background: Caring for Alcohol Dependence Syndrome (ADS) patients significantly impacts caregivers’ quality of life (QOL). This study, rooted in Lazarus and Folkman’s Transactional Model, explores the pivotal role of family functioning (FF) in navigating caregiving stressors. Materials and Methods: A sample of 128 primary caregivers for ADS patients were collected from two psychiatric hospitals in Amritsar, Punjab. Data were collected using assessment tools such as the World Health Organization QOL–BREF and Family Assessment Device and were analyzed through Pearson product-moment correlation and regression analysis. Results: Negative correlations across various FF domains in caregivers were observed, emphasizing the pervasive impact of family dynamics on well-being. The overall FF score demonstrated significant negative associations with specific QOL dimensions, indicating the multifaceted influence of FF. In addition, the linear regression analysis highlighted the robust predictive capacity of the overall FF score in influencing caregivers’ QOL (β = −0.603). FF contributed significantly, explaining 36% of the variance in QOL among ADS caregivers. Conclusions: Addressing challenges in specific FF domains, such as problem-solving and communication, can enhance overall QOL. The robust predictive capacity of the overall FF score emphasizes the need for holistic approaches, urging clinicians to integrate family-focused interventions into ADS treatment plans.